Implementing Integrated Islamic Religious Education to Foster Critical Thinking Skills: A Qualitative Study at SMA IT Raudhatul Ulum Sakatiga - Mun'im, Abdal; Arqam, Mhd. Lailan; Rahman, Arif; Sutipyo, Sutipyo; Khaerudin, Khaerudin (Early Publishing, 2025)
Islamic Religious Education (IRE) learning in many secondary schools is still dominated by teacher-centered instruction and memorization-oriented practices, which limit students’ opportunities to develop critical thinking skills. This study aims to explore how integrated Islamic Religious Education is implemented to foster students’ critical thinking abilities. Using a qualitative case study design, the research was conducted at SMA IT Raudhatul Ulum Sakatiga. Data were collected through in-depth interviews, classroom observations, and document analysis involving Islamic Religious Education teachers, students, and school administrators. The findings reveal that integrated IRE is systematically implemented through contextual instructional planning, dialogical and problem-based learning strategies, and reflective formative evaluation. These learning practices encourage students to analyze real-life issues, articulate arguments, and reflect critically on Islamic values. The learning process also supports students’ autonomy, competence, and relatedness, which strengthens intrinsic motivation and active cognitive engagement. In conclusion, integrated Islamic Religious Education effectively promotes students’ critical thinking skills while maintaining moral and spiritual values. Therefore, integrated IRE represents a relevant and effective pedagogical model for enhancing Islamic education learning in response to contemporary educational challenges.